The Study of Milk Fever Disease and Its Treatment and Prevention Methods in Dairy Cows - Habibi, Emal (Journal of Natural Sciences – Kabul University, 2020)
Milk fever is one of the metabolic diseases that causes significant economic losses to farmers and the livestock industry annually. Despite its name, milk fever does not involve a fever. It results from a decrease in blood calcium levels during parturition or shortly thereafter, with the onset of lactation. Symptoms include no fever, sudden paralysis, loss of consciousness, and coma, and if left untreated, the condition can lead to death. Diagnosis is typically based on the clinical signs of the disease. The treatment of milk fever involves the administration of calcium supplements, especially calcium borogluconate, with intravenous injection being the fastest method. Various methods are used to prevent milk fever, but diet regulation is the most commonly used approach.